Tawhid as a Framework for Psychological Resilience in the Crisis of Meaning: A Double Movement Hermeneutic Study of Surah Al-Baqarah 2:38 and 2:286 - Nur Fadilah Ramadhany; Tulus Musthofa; Maragustam Siregar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
The rising prevalence of depression in modern society is not only driven by biological, psychological, and social factors, but also by a growing crisis of meaning shaped by secular culture and materialistic life orientations. This loss of existential purpose intensifies psychological vulnerability and contributes to anxiety and depressive conditions. From an Islamic perspective, tawhid offers a transcendental, stable, and comprehensive foundation of meaning for human existence. This study aims to reconstruct tawhid as a meaning-based framework for psychological resilience through Fazlur Rahman’s Double Movement hermeneutic analysis of Qur’an 2:38 and 2:286, integrated with contemporary theories of meaning psychology. The findings demonstrate that tawhid functions as a meaning-making system that shapes life orientation, fosters hope, reduces existential anxiety, and promotes acceptance of human limitations. The principle of divine guidance in Qur’an 2:38 and the concept of proportional divine justice in Qur’an 2:286 form a structure of psychological resilience capable of addressing the modern crisis of meaning. This study argues that tawhid should be understood not merely as a theological doctrine, but as a meaning-based psychological resilience framework. However, this research remains limited to a conceptual and literature-based approach focusing on two Qur’anic verses, thus requiring further empirical validation in future studies.